Ответ(ы) на вопрос:
Гость
3х-3+2х²+2х-5х-5 (х²+1)(х²-1) 2х²-8 (х²+1)(х²-1)
= ----------------------- * ----------------- = ------------- * ------------------ = х²+1
х²-1 2х²-8 х²-1 2х²-8
Гость
[latex]3)\; \left ( \frac{3}{x+1} + \frac{2x-5}{x-1} \right)\cdot \frac{(x^2+1)(x^2-1)}{2(x^2-4)} = \frac{3(x-1)+(2x-5)(x+1)}{(x+1)(x-1)} \cdot \frac{(x^2+1)(x^2-1)}{2(x^2-4)} =\\\\= \frac{3x-3+2x^2+2x-5x-5}{(x^2-1)} \cdot \frac{(x^2+1)(x^2-1)x}{2(x^2-4)} = \frac{2x^2-8}{x^2-1} \cdot \frac{(x^2+1)(x^2-1)}{2(x^2-4)}=\\\\= \frac{2(x^2-4)\cdot (x^2+1)}{2(x^2-4)} =x^2+1\\\\1)\; \; (b+2a)(2a-b)=(2a-b)(2a+b)=(2a)^2-b^2=4a^2-b^2\\\\P.S.\; \; (a-b)(a+b)=a^2-b^2\\\\(a-b)(a+b)=(a-b)(b+a)=(b+a)(a-b)=a^2-b^2[/latex]
Внимательно используйте формулу разности квадратов !
Не нашли ответ?
Похожие вопросы